The Trade Creation Effect of Immigrants: Testing the Theory on the Remarkable Case of Spain - Giovanni Peri; Francisco Requena (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
There is abundant evidence that immigrants' networks are associated with larger trade flows between countries of origin and the country (or province) where they settle. The causality of such relation and its magnitude, however, have not been proven beyond reasonable doubt. We use the simple predictions of the model by Chaney (2008) and treat networks of migrants as a device that reduces fixed bilateral trade costs. In so doing we have strong predictions on the effect of immigrants on total exports, exports by category of goods, and on the extensive and intensive margin of trade. We test these predictions using the remarkable and uneven increase of immigration to Spanish provinces between 1993 and 2008. The richness of our data, a panel of import and export by sector between 50 Spanish provinces and 77 countries over fifteen years, allows us to control for a very large set of covariates and fixed effects and to use an instrumental variable strategy so that we can isolate the trade-creation effect of new immigrants. We are also able to qualify the effect of immigration on bilateral trade of homogeneous and differentiated goods, and its impact on the intensive and extensive margin of trade. Our findings support all the implications of the Chaney model showing that migration network indeed seems to decrease the fixed costs of trade. Finally by decomposing the effect across provinces and over time we find evidence that the elasticity of trade creation to new immigrant is larger once a critical mass has been reached.
Keywords: F21; F22; 330